AC load flow calculation of power system - Wan Kit Peng (Universiti Malaysia Perlis, 2009)
This final year project presents the AC load flow calculation of power system by using the Delphi 7 as the development tool to develop the project. Delphi is a completely a new program with new graphical user interface and new computational engine. This software calculation will provide user for computing AC load flow calculation comprise Gauss-Seidel, Newton-Raphson and Fast-Decoupled method. Besides that, a graphical user interface (GUI) was developed to maximize flexibility for user when using this software calculation. Finally, this software calculation is hoped to bring a lot of benefits and flexibility for user in the process of the AC load flow calculation.